Dysphagia as an early presentation of Di George's Syndrome- case report - Palchevska, Snezana; Gjurkova, Beti; Shukarova, Elena; Stavrikj, Katarina; Jovanovska, Jana; Aluloska, Natasha (Institute of Public Health of the Republic of Macedonia/Scientific Foundation SPIROSKI, 2021)
DiGeorge’s syndrome is a 22q11.2 deletion leading to abnormal embryogenesis of pharyngeal arches and it is manifesting in a variety of clinical signs and symptoms. The spectrum of anomalies varies from minor facial dysmorphism and cleft palate to a broad spectrum of cardiovascular anomalies, thymic disfunction and immune deficiencies, hypocalcemia due tohypoparathyroidism,growth and developmental delay and speech disturbances. Cardiovascular anomalies might include right sided aortic arch, aberrant vesiclesand vascular ring. Here we present an atypical case of partial DiGeorge’s syndrome with feeding and swallowing difficulties and laryngeal stridor in the neonatal period. Early presentation in this period is usually due to severe hypocalcemia and cardiac disease. Feeding difficulties in a preterm baby needed clinical assessment skills in order to establish the diagnosis and delineate it from feeding difficulties usually seen in preterm babies. Esophagogram (barium X Ray) showed antero-posterior oblique impression towards the right side, the latero- lateral view showed impression on the rare side, suspected to be esophageal sub stenosis due to vascular anomaly, aberrant right subclavian arteryand suspectedthymic hypoplasia. We report a 9-year follow up periodbya team of subspecialists. The child had two surgeries due to aberrant vessel and velopharyngeal deficiency. Optimal management of patients with DiGeorge’s syndrome requires a multidisciplinary teamwhichshould include a cardiologist, immunologist, geneticist, speech/language therapist, endocrinologist and other subspecialists depending on patient`'s phenotype.